IMPLEMENTATION OF THE ACCOUNTING RECORDING AND REPORTING SYSTEM AT PT. SINAR ABADI KREATIFINDO - Jessica Yeo; Meiliana Suparman (ConCEPt - Conference on Community Engagement Project, 2022)
The financial statements of a company provide information that is essential for business owners to make informed decisions. PT. Sinar Abadi Kreatifindo is a partner of this community service. The company is an interior design firm. In the past, the company recorded financial transactions manually and used MS Excel, for example, when it was managing accounts receivable. Due to this condition, frequent recording errors occur and financial reports cannot be generated. This project is aimed at providing PT PT. Sinar Abadi Kreatifindo with an information system based on MS Access that can provide accurate financial reports. Data were obtained through observation, interviews, document reviews from partners, as well as literature reviews. The accounting information system provided is designed in accordance with EMKM accounting standards to help partners record financial transactions more easily. The system is capable of generating statements of financial position, income statements, statements of change in equity, and cash flow statements. Furthermore, partner can also view and/or produce a list of completed and on-going projects, a list of customers, and its receivables. This project allows partner to obtain accurate financial information and reinforces internal controls. The system designed by the author is still relatively simple and can still be improved both in terms of design and the reports produced.